2020
DOI: 10.1021/acsnano.9b08162
|View full text |Cite
|
Sign up to set email alerts
|

Band Depopulation of Graphene Nanoribbons Induced by Chemical Gating with Amino Groups

Abstract: The electronic properties of graphene nanoribbons (GNRs) can be precisely tuned by chemical doping. Here we demonstrate that amino (NH 2 ) functional groups attached at the edges of chiral GNRs (chGNRs) can efficiently gate the chGNRs and lead to the valence band (VB) depopulation on a metallic surface. The NH 2 -doped chGNRs are grown by onsurface synthesis on Au(111) using functionalized bianthracene precursors. Scanning tunneling spectroscopy resolves that the NH 2 groups significantly upshift the bands of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 55 publications
0
26
1
Order By: Relevance
“…9b ). 200 A recent study conducted by Li et al 216 showed that edge functionalization can even act to partially depopulate the valence band through hole doping ( Fig. 9c ).…”
Section: Electronic Properties Of Graphene Nanoribbonsmentioning
confidence: 97%
“…9b ). 200 A recent study conducted by Li et al 216 showed that edge functionalization can even act to partially depopulate the valence band through hole doping ( Fig. 9c ).…”
Section: Electronic Properties Of Graphene Nanoribbonsmentioning
confidence: 97%
“…40,41 Functionalization of GNRs with cyano, fluoro, and amino groups has been reported through the on-surface method, but pre-installed functional groups are often removed during the cyclodehydrogenation on metal substrates, prohibiting efficient synthesis of edge-functionalized GNRs. [42][43][44][45] Through edge functionalization with electron-donating or -withdrawing groups, it becomes possible to modulate the electronic properties of GNRs, including the position of energy levels and bandgap. 42,43,[46][47][48][49] Moreover, the planarity of GNRs can also be altered by inducing steric repulsion.…”
mentioning
confidence: 99%
“…[42][43][44][45] Through edge functionalization with electron-donating or -withdrawing groups, it becomes possible to modulate the electronic properties of GNRs, including the position of energy levels and bandgap. 42,43,[46][47][48][49] Moreover, the planarity of GNRs can also be altered by inducing steric repulsion. To this end, we have recently synthesized planar and non-planar GNRs with the identical aromatic core structure by installing alkyl chains at different peripheral positions, causing steric congestion with neighboring aromatic protons.…”
mentioning
confidence: 99%
“…The role of the chlorine substituents, on the other hand, is to reduce the temperature of the final interribbon lateral cross‐coupling in order to assure the survival of the pyrimidine group throughout all the reaction sequence. We do that by substituting the dehydrogenative CC coupling that requires temperatures of ≈450 °C, [ 28 ] high enough to cleave or decompose edge functional groups, [ 20,21 ] by a HCl zipping mechanism that emulates the recently reported HF zipping and can already be triggered at the CDH reaction temperature of 300 °C. [ 31,32 ] This reduction of 100 °C, as compared to the HF zipping observed on the same surface, is crucial for the synthesis of heterogeneous structures as the one demonstrated in this work, since most heterogeneous moieties cannot withstand the 400 °C needed for the HF zipping.…”
Section: On‐surface Synthesis Of the Nanoporous Graphenementioning
confidence: 99%
“…[ 31,32 ] This reduction of 100 °C, as compared to the HF zipping observed on the same surface, is crucial for the synthesis of heterogeneous structures as the one demonstrated in this work, since most heterogeneous moieties cannot withstand the 400 °C needed for the HF zipping. [ 19,20 ] We envision that this temperature reduction can also be crucial to promote the synthesis of covalent nanostructures on less reactive insulator surfaces, as recently demonstrated by using the HF zipping. [ 31 ]…”
Section: On‐surface Synthesis Of the Nanoporous Graphenementioning
confidence: 99%